PENGARUH EKSTRAK Annona muricata L. TERHADAP KADAR UREUM DAN KREATININ SERUM TIKUS WISTAR YANG DIINDUKSI DIET TINGGI LEMAK DAN TINGGI FRUKTOSA - Nuril Amalia Novianti (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2019)
Introduction: hyperlipidemia is a risk factors of atherosclerosis which occur in the renal aeteries can caused kidney impairment. Soursop leaves (Annona muricata L.) has a potential as antihyperlipidemia. The purpose of this study was to determine the effects of Annona muricata L. extract towards the ureum and creatinine serum levels in wistar rats induced by high fat and fructose diet (HFFD).Method: The study used a post test control group only design with an experimental laboratory method in vivo. 25 Wistar rats aged 8-10 weeks and the initial weight of 175-200g were divided into 5 groups; Negative Control (KN), Positive Control (KP), Treatment group 1 (100mg / kgB.W), Treatment Group 2 (200 mg / kgB.W), and Treatment Group 3 (400 mg / kgB.W). DLTF induction was given at the KP and Treatment Group simultaneously with herbs for 10 weeks. Examination of serum urea and creatinine using the colorimetric method with a wavelength of 600 nm and 510 nm in the spectrophotometer. Data analysis using SPSS version 20 with a significance level at p<0.05.Results: Plasmatic ureum level was 13,22±0,90 mg/dL, 16,12±12,24 mg/dL, 11,28±3,65 mg/dL, 7,64±0,93 mg/dL, dan 7,2±2,03 respectively in KN, KP, KP1, KP2, and KP3. Plasmatic creatinine level was 0,58±0,04 mg/dL, 0,68±0,13 mg/dL, 0,58±0,08 mg/dL, 0,48±0,04 mg/dL, dan 0,5±0,07 mg/dL respectively in KN, KP, KP1, KP2, and KP3. Plasmatic creatinine level of KP2 and KP3 had significantly lower than KP (p<0.05).Conclusion: The addition of Annona muricata L. decreased plasmatic creatinine level in hyperlipidemic rats.Keywords: hyperlipidemia, Annona muricata L. extract, urea and creatinine